Deklaracje bońsko-kopenhaskie jako wzór regulacji prawnych wobec mniejszości narodowych we współczesnej Europie = The Bonn-Copenhagen declaration as a model of legislation regarding national minorities in contemporary Europe - Husak, Bogumiła (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the essential political questions of contemporary Europe concerns the policy of the EuropeanUnion with regards to its various national minorities and ethic groups. Relations between a majorityand minorities are often characterized by antipathy and discrimination, rather than by toleration,egality and openness to the Other.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia